Entropy generation analysis due to heat transfer and nanofluid flow through microchannels: a review. (28th January 2020) - Kumar, Krishan; Kumar, Rajan; Bharj, Rabinder Singh
This work presents a detailed review of the entropy generation due to the heat transfer and the fluid flow through different channels. The earlier contribution of the researchers in the form of theoretical, numerical and experimental studies on the entropy generation in the conventional or microchannels, with or without disruption in the flow and with or without the use of nanofluids is reviewed. The brief discussion on the microchannels, disrupted microchannels, nanofluids and entropy generation is presented. Studies performed on the channel cross-sectional shapes and rib shapes for thermal performance optimisation are discussed in the paper. Nanoparticles such as Al2 O3, Cu, CuO, Ag, SiO2, etc. have been used for preparing the nanofluids along with water, ethylene glycol, etc. as base fluids. Additionally, the effect of disruption in flow field on the entropy generation is also discussed. The disruptions in the form of ribs, cavities, vortex generators, etc. have been taken into account. It is hoped that this review article can provide a basis for further research on the irreversibility analysis of the nanofluid flowing through disrupted microchannels to improve the hydrodynamic and thermal performance of the system.